Indonesian Diaspora movement and citizenship law reform: towards 'semi-dual citizenship'*. Issue 1 (2nd January 2019) - Dewansyah, Bilal
ABSTRACT: The movement of 'Indonesian Diaspora' abroad has shown significant institutionalized progress since the establishment of Indonesian Diaspora Network (IDN) in 2012. The central issue is that Indonesian diaspora is demanding the recognition of dual citizenship from Indonesia, while Act No. 12/2006 regarding Citizenship (Citizenship Law), recognizes the principle of a single nationality and limited dual citizenship only for children. However, the dual citizenship proposal has not yet been politically acceptable, not only because of the historical experience in the past, but also because of the constitutional identity aspect on single citizenship policy. Therefore, the immigration privilege and recognition of some legal rights, excluding some political rights and citizen rights, are practical solutions that are most likely to be adopted for Indonesian diaspora. I call this proposal as 'semi-dual citizenship'. This article elaborates this proposal with special reference to the Indian experience in the context of ongoing debate over Citizenship Law amendment and also to certain immigration legislation. As a dynamic concept, 'semi-dual citizenship' scheme can be seen as a 'diaspora test' for Indonesian diaspora that can be gradually developed depending on how this legal scheme can be workable to maintain their social ties with Indonesian society.